Project Supply Chain Management in Product Development: Study of Literature and its Development - S. Salmiah; Ana Rusmardiana; Andi Desfiandi; Aswin Aswin; Febrianty Febrianty; Andi Reni; Abdul Nesser Hasibuan; Iswandi Idris; Muhammad Rafiq (International Journal of Supply Chain Management, 2020)
Abstract— The focus on logistics and supply chain management in most industries is as means for improving the competitiveness of the industry or companies. It is require developing a project supply chain management that reduces its cost, process and product development time, to stand in the market also not lose the benefits in the global market. To achieve a process and product that have low cost and improved quality there is requirement of combining project management techniques with current engineering resources. A good product team always works on the improvement of product quality, efficiency and cost effectiveness. They know that there are always new and innovative ideas are implemented. It is require setting the priorities of these ideas. This paper studies the different approaches of project supply chain management to developing a good product. There are many challenges faced by the developer to grow and expanding the products.